Profil Pedagang Buah-Buahan di Pasar Adat Blahkiuh Kecamatan Abiansemal Kabupaten Badung - MAHESWARI, ANAK AGUNG SAGUNG SARI; ARTINI, NI WAYAN PUTU; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p34, 2022)
Profiles of Fruit Traders in Blahkiuh Traditional Market, Abiansemal District,  Badung Regency.  Fruit traders have a big role in marketing agricultural products. This study aims to determine the profile of fruit traders and the income from fruit trading business in the Blahkiuh Traditional Market, Abiansemal District, Badung Regency. The selection of the research location was done purposely and the selection of 38 respondents was done using simple random sampling. Primary data were obtained from questionnaires-guided interviews with fruit traders. Secondary data were obtained from relevant literature. Based on the study, the profile of fruit traders in the Blahkiuh Traditional Market is identified, namely, (1) in terms of identity, all of the fruit traders are women, most of whom have basic education, (2) in terms of trade networks, traders get a supply of local fruit from the island of Bali and Java and imported fruits from China, (3) in terms of the characteristics of the trading business, the capital comes from own savings and all traders work an average of 7 hours per day. The average income of fruit traders in the Blahkiuh Traditional Market is IDR 4,220,521.62 per month.